Investigation of electrical, dielectric and interface state densities of Al/p-Si structures with PTCDA interlayer under different light intensities - Karatas, Sukru; Canli, Fatih; Yakuphano glu, Fahrettin (Elsevier, 2024)
In our study; we investigated illumination intensity-dependent electrical and dielectric properties of the Al/ptype Si metal-semiconductor (MS) structures with perylenetetracarboxylic dianhydride (PTCDA) interface using current-voltage (I-V) and capacitance-conductance-voltage (C-G/omega-V) measurements. Thin film layer with PTCDA interface was coated on p-type Si by Spin Coating method. The structure of PTCDA organic semiconductor powder examined by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The electrical parameters such as ideality factors (n), barrier heights (obo), rectification ratios (RR), saturation currents (I0) and series resistances (RS) were obtained from both thermionic emission (TE) theory and Cheng theory and compared with each other. Dielectric properties such as dielectric constant (e'), dielectric loss (e), loss tangent (tan6), electrical conductivity (oac), and interface state densities (NSS) were obtained from C-V and G/omega-V measurements. It was seen that the values of epsilon ', epsilon, tan delta, and NSS decreases with increasing illumination while sigma ac increase with increasing illumination intensity. Experimental results show that Al/PTCDA/p-type Si semiconductor structure can improve efficiency in electronic devices.
Keywords: Electric and dielectric properties; Illumination intensity; PTCDA; Electrical conductivity